The Effect of E-Portfolio in Project-Based Learning toward Learner Autonomy and Writing Competency - Devi Ariningsih, Ni Ketut; Artini, Luh Putu; Marsakawati, Ni Putu Era (Journal of Education Reseach and Evaluation, 2021)
The National Education objectives can be achieved through learning process and a valid assessment process. Assessment has a strong involvement in the learning process. The purpose of this study is to investigate the effect of e-portfolio in project-based learning toward learner autonomy and writing competency experienced by X MIPA students of SMA Negeri 7 Denpasar. The research design was post-test only control group design. The research instruments used were questionnaire and writing test. Questionnaire was used to test learner autonomy, while writing test was used to test students’ writing competency. Data were analyzed by employing One-way Anova and Manova. The results of this study showed that there is a significant effect of E-portfolio in Project-Based Learning toward learner autonomy and writing competency of X MIPA students of SMA Negeri 7 Denpasar. The mean score of students who were taught by using e-portfolio in project-based learning strategy is higher than the mean score who were taught by using conventional strategy. E-portfolio in Project-Based Learning also revealed potentially promotes students’ creativity, problem solving skills, and communication through technology skills.